Dinamična analiza deformiranja cestne varnostne ograje pri naletu vozila - Vesenjak, Matej (Strojniški vestnik, 2003)
This paper describes a dynamic analysis of a steel road-restraint system that is used on public roads to prevent a vehicle from veering off the road or breaking through to the opposite side of the road. The European standard EN 1317 provides the exact criteria that the road-restraint system has to fulfill. Practical observations of installed systems indicate that the currentdistance spacer is too stiff, which results in unacceptable decelerations during vehicle impact. The stiffness of the restraint system in the initial phase of the crash is largely attributed to the distance-spacer design. The purpose of this research was to evaluate new designs of the distance spacer with increased crash-energy absorption due to a more controlled deformation during vehicle impact. The stiffness of various designswas evaluated with nonlinear dynamic (material, geometric and structural-contact nonlinearity) analysis of a three-dimensional road-restraint system within the framework of the finite-element method. The computational analyses prove that the currently used distance spacer is indeedfar too stiff and that the new designs ensure controllable elasto-plastic deformation and absorb more crash energy, which in turn reduces decelerations during the impact and increases the safety of road users.
Keywords: varnost na cestah; ograje varnostne; analize dinamične; simuliranje numerično; simuliranje nelinearno; varnostne ograje; similacije; dinamična analiza; zdrs